2010
DOI: 10.1111/j.1365-2591.2010.01704.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of neuropeptide Y Y1 receptors during pulpal inflammation

Abstract: This study gives evidence that Y1R is a modulator of pulpal inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Neuropeptide‐Y1R is a multifunctional receptor with previously reported effects such as vasoconstriction, vascular permeability, nociception, and immune modulation (25, 26, 57, 58). Our results substantiate previous studies indicating that NPY‐Y1R is a major modulator of immune/inflammatory responses (59, 60). Effective migration of innate immune cells depends on cytoskeleton remodeling (61), and recent studies demonstrated that MAPK phosphorylation activates this remodeling (62).…”
Section: Discussionsupporting
confidence: 92%
“…Neuropeptide‐Y1R is a multifunctional receptor with previously reported effects such as vasoconstriction, vascular permeability, nociception, and immune modulation (25, 26, 57, 58). Our results substantiate previous studies indicating that NPY‐Y1R is a major modulator of immune/inflammatory responses (59, 60). Effective migration of innate immune cells depends on cytoskeleton remodeling (61), and recent studies demonstrated that MAPK phosphorylation activates this remodeling (62).…”
Section: Discussionsupporting
confidence: 92%
“…Y1R has also been reported to be involved in many physiological activities, such as mitogenic activity, macrophage migration, and pulpal development ( 17 , 21 , 22 ). In bone tissue, Y1R is highly expressed in BMSCs, osteoblast, osteocyte, monocyte/macrophage, and osteoclast ( 2 ), prompting it to play a regulatory role in the local area.…”
Section: Neuropeptide Y and Its Receptorsmentioning
confidence: 99%
“…In line, enrichment for Biological Process revealed "leukocyte mediated immunity", "neutrophil mediated immunity" and "neutrophil activation". Together, these analysis are indicative of ongoing activation and neutrophil degranulation, and supportive of the observed subclinical pulpal inflammation 9 , enhanced emigration of neutrophils into the inflamed pulp 10,11 and increased numbers of degranulated neutrophils in periodontitis patients 14 . It is thus likely that "neutrophil degranulation" is a confounding element of the salivary protein signature of MIH patients, reflecting ongoing inflammation.…”
Section: Discussionmentioning
confidence: 57%